What happened to the Ekottarikāgama 增壹阿含經 T125 after the death of Dao'an? - Radich, Michael; Norrish, Jamie (International journal of Asian studies, 2025)
The only extant complete Ekottarikāgama, viz. Zengyi ahan jing 增壹阿含經 T125, has presented modern scholarship with significant challenges. This study departs from the assumption, demonstrated in prior work, that the extant collection is due to *Dharmanandin and Zhu Fonian (and not Saṅghadeva, as wrongly held by tradition and the Taishō). The study first systematically reviews and coordinates prior scholarship on a number of possible anomalous features of T125, such as possible Mahāyāna-ish elements, Sarvāstivādin elements, merged discourses, and material found only late in Pāli and other mainstream canonical parallels. We show that these anomalies are not evenly distributed, but cluster in certain patches of the collection. The second part of the study then presents new, internal (stylistic) evidence that shows that these anomalies tend to be correlated with evidence that associates some discourses in the collection with Zhu Fonian's style in original works, and with later texts. On this basis, we argue that the collection underwent modification after the death of Dao'an 道安 in 385, and suggest, more speculatively, that some of these modifications likely stemmed from the hand of Zhu Fonian.
Gesehen am 03.12.2025